What do Students Know About Green Chemistry? Evidence from a Survey of Pre-Service Chemistry Teacher - Julia Mardhiya; Lenni Khotimah Harahap (Chemistry Education Department, 2022)
The application of Green Chemistry (GC) is increasing at the university level. This study focuses on measuring the knowledge of pre-service chemistry teachers about the principles of GC. The instrument used is the Assessment of Student Knowledge of Green Chemistry Principles (ASK-GCP). The instrument is 24 questions in multiple true-false formats about the principles of GC. The data were collected between May and June 2022. The total sample was 90 students. The data was analyzed using Rasch Model with Winsteps 5.1.2. The interaction between the person and the item shown on the Wright map. 44.5% of students in the high category of knowledge about GC. The result of this survey can be used as a reflection for students and instructors about GC knowledge.